Perancangan Interior House of Honey Surabaya - Winnona Natasha A.; Cok Gede Padmanaba; Grace Mulyono (Intra, 2016)
Indonesia was a country where producing various honey , it was because Indonesia is a tropical countries where growing various flowers that is a source of food of the honeybee. Actually Indonesian’s honey have a very good potential, Indonesia have many species of bee and kinds of flowers that will to affect the color and the sense of honey. But most honey that marketed in Indonesia is a honey of cattle bee that the food has been provided beforehand so that reduced the quality of honey is. Honey with the best quality only can be enjoyed by a narrow segment of society that really understand honey .Therefore , one way introduce honey to Indonesian people is to design a honey house. Honey house is a public facilities that can became a learning tools , knowledge , trading , recreation and a facility where people indonesia can know and study various types of honey and benefits of honey Indonesia. This honey house established with a view to introduce what and how the honey made .